Effect of hyperbaric oxygen therapy on peripheral blood inflammatory markers in patients with neuromyelitis optica spectrum disorder: a retrospective cohort study - Pan, Liya; Mo, Yanming; Wei, Yulan; Luo, Shisheng; Wu, Yuan (Frontiers in Neurology, 2025)
BackgroundNeuromyelitis optica spectrum disorder (NMOSD), an AQP4-IgG-mediated central nervous system demyelinating disease, is prone to recurrent disability. Although the anti-inflammatory and neuroprotective effects of hyperbaric oxygen therapy (HBOT) in neurological diseases have been reported, its immunological impact on NMOSD remains poorly understood.ObjectiveTo evaluate the effect of HBOT on peripheral inflammatory markers in patients with NMOSD and explore its potential immunomodulatory role.MethodsThis retrospective cohort study included 36 NMOSD patients diagnosed between January 2022 and December 2024, divided into an HBOT plus standard treatment group (n = 18) and a standard treatment-only group (n = 18). Peripheral blood samples were collected before and after treatment to assess the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte counts. Paired tests and ANCOVA (adjusted for baseline values) were used to compare within-group and between-group differences.ResultsAfter a median of 12 HBOT sessions, the HBOT group showed a 31.78% increase in lymphocyte count (Δ = +0.41 × 109/L, 95% CI: 0.05–0.77), and significant reductions in NLR by 18.98% (Δ = −0.52, 95% CI: −1.02 to −0.02) and PLR by 17.97% (Δ = −37.21, 95% CI: −69.15 to −5.27). After adjustment, the HBOT group demonstrated significantly greater improvements in NLR (−55.56%) and PLR (−22.79%) compared to the control group (both Bonferroni-corrected P < 0.01). Subgroup analysis revealed that patients with baseline NLR ≥ 3 benefited the most (interaction P = 0.038). No serious adverse events were observed.ConclusionHBOT may help rebalance the immune system in NMOSD by increasing lymphocyte counts and reducing NLR and PLR, potentially contributing to immune modulation. These findings support the potential of HBOT as an adjunctive therapy for NMOSD, particularly in patients with a high inflammatory burden. Larger prospective studies are warranted to confirm its long-term efficacy and underlying mechanisms.